2012
DOI: 10.2147/opth.s35321
|View full text |Cite
|
Sign up to set email alerts
|

Near-infrared fundus autofluorescence-visualized melanin in the choroidal abnormalities of neurofibromatosis type 1

Abstract: Purpose:To report a series of three cases of neurofibromatosis type 1 examined by near-infrared fundus autofluorescence (NIR-AF) with a scanning laser ophthalmoscope and spectral-domain optical coherence tomography (OCT) to show the characteristics of choroidal abnormalities.Methods:Retrospective case series. Six eyes of three patients were examined by conventional fundus examinations, near-infrared monochromatic light reflectance (NIR-R) and NIR-AF, OCT, fluorescein angiography, and indocyanine green angiogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…5 Among the cases of our cohort it is noteworthy that the patient with NF-1 clinical diagnosis had both normal FAF and SD-OCT images, as opposed to IR sequences in which striking hyperreflective patches were identified in the posterior pole, as it has previously described in NF-1. 9 Furthermore, in LORD patients, while in the advanced stage the FAF already detects fine perimacular mottling, in the incipient stage the FAF was normal but the SD-OCT and the BR and GR of the MCI showed numerous reticular pseudodrusen. As reticular pseudodrusen are a common finding in patients with age related macular degeneration and associated with a higher risk of development of choroidal neovascularization, 10 MCI may be also useful in this field.…”
Section: Discussionmentioning
confidence: 98%
“…5 Among the cases of our cohort it is noteworthy that the patient with NF-1 clinical diagnosis had both normal FAF and SD-OCT images, as opposed to IR sequences in which striking hyperreflective patches were identified in the posterior pole, as it has previously described in NF-1. 9 Furthermore, in LORD patients, while in the advanced stage the FAF already detects fine perimacular mottling, in the incipient stage the FAF was normal but the SD-OCT and the BR and GR of the MCI showed numerous reticular pseudodrusen. As reticular pseudodrusen are a common finding in patients with age related macular degeneration and associated with a higher risk of development of choroidal neovascularization, 10 MCI may be also useful in this field.…”
Section: Discussionmentioning
confidence: 98%
“…The prevalence of choroidal nodules detected by NIR was 71% in the paediatric population, a much higher frequency than the NIH ophthalmic diagnostic criteria of 43% for iris Lisch nodules [ 14 ]. Subsequent literature published on the topic confirmed NIR as a valid and reliable diagnostic imaging method in revealing choroidal abnormalities with a very high interobserver agreement in NF1 patients [ 15 17 ].…”
Section: Neuro-oculocutaneous Syndromes/phakomatosismentioning
confidence: 99%
“…The cutoff value for choroidal nodules that can be detected by NIR was reported to be 1.5 [2]. Different imaging modalities, including NIR, near-infrared autofluorescence and optical coherence tomography (OCT), demonstrated that the choroid is affected by NF1 [3, 4, 5]. …”
Section: Introductionmentioning
confidence: 99%